Pengaruh Kualitas Layanan Terhadap Ulasan Wisatawan Serta Implikasinya Pada Kunjungan Wisatawan Pada Objek Wisata Alam Di Curug Cikondang Cianjur - Muhammad Iqbal Risman; Wentri Merdiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of service quality on tourist reviews and its implications for tourist visits to the Curug Cikondang natural attraction in Cianjur Regency. The research adopts a quantitative approach using the path analysis method. The main variables examined include Service Quality (X), Tourist Reviews (Y), and Tourist Visits (Z). The population comprises all tourists who have visited Curug Cikondang, with a total of 100 respondents selected using purposive sampling. Data were collected using a Likert-scale questionnaire (1–5) and analyzed through SPSS version 25.0. The results indicate that service quality has a positive and significant effect on tourist reviews, tourist reviews have a positive and significant effect on tourist visits. Service quality has a positive but insignificant direct effect on tourist visits and tourist reviews act as a significant mediating variable between service quality and tourist visits (Sobel test Z = 4.255, p < 0.05). These findings demonstrate that digital reviews play a crucial mediating role between on-site service experiences and tourist visit decisions. Practically, it is recommended that the Curug Cikondang management improve service quality, enhance infrastructure, and actively manage digital reviews to strengthen the destination image and foster tourist loyalty.